Consumo de energia específica de corte em madeiras de diferentes densidades em distintas umidades - Guedes, Taiane Oliveira (2016)
Searches for proper use of energy during wood processing industry are of interest, since it is necessary to know the best relationship between the required energy and raw material of wood processed. The objective of this study was to evaluate the energy performance required in the mechanical processing of wood with different densities and moistures. The mechanical processing was done with router programmed by Computer Numerical Control (CNC), which allowed control of the cutting speed and feeding speed. Three woods were processed species of Pinus spp., Goupia glabra (Cupiúba) and Dipteryx alata (Cumaru vermelho) were processed with different humidities moistures contents, which were established through continuous drying. Every in each stage of humidity moisture the samples were processed, totaling eight stage in each specimen. For the specific energy consumption in each processing is it was used the energy analyzer, Fluke mark. The lowest average values of specific cutting energy were 299, 262 and 292 KJ.cm -3 for the timber Cumaru (36%), Cupiúba (71%) and Pinus (85%), respectively. The highest average values of required energy were 570, 513 and 497 KJ.cm -3 , all to 0% humidity moisture and for wood Cumaru, Cupiúba and Pinus, respectively. The energy values close to the fiber saturation point were 416, 397 and 359 KJ.cm -3 to Cumaru, Cupiúba and Pinus, respectively. It was observed increase of 70 KJ.cm -3 (12%) in the power cut wood of Cumaru to for 4% drop in humidity moisture. For wood Cupiúba the increase was 67 KJ.cm -3 (13%) to for 12% drop in humidity moisture and the wood of for Pinus the increase was 54 KJ.cm -3 (11%) to for 8% drop in humidity moisture. Woods with higher humidity moisture content requisitioned demanded lower specific power cut. The energy analyzer allowed to obtain the data satisfactorily, errors attributable due to the acquisition rate did not affect the analysis.